Early Empiric Antibiotic Use Is Associated With Delayed Feeding Tolerance in Preterm Infants: A Retrospective Analysis. Issue 1 (July 2017) - Martinez, Francisco E.; Ferri, Walusa A.G.; Leone, Clea R.; de Almeida, Maria Fernanda Branco; Guinsburg, Ruth; Meneses, Jucille do Amaral; Vale, Marynéa Silva do; Marba, Sergio Tadeu Martins; de Carvalho, Werther Brunow; de Souza Rugolo, Ligia Maria Suppo; de Andrade Lopes, José Maria; Ribeiro, Manoel A.; et al.
Abstract : ABSTRACT: The causative factors of neonatal feeding intolerance are poorly understood, but potentially related to clinical practices such as empiric antibiotic usage. The objective of this study was to evaluate whether early empiric antibiotic exposure negatively affects preterm infants' enteral feeding tolerance. Data from infants without risk factors for sepsis, 500 to 1499 g birth weight and 24 to 34 weeks gestational age were analyzed. The primary outcomes were the empiric antibiotic exposure effects on the infants' total parenteral nutrition usage duration and prevalence of necrotizing enterocolitis (NEC). Among the 901 infants included, 67 were exposed to early empiric antibiotic. A 50% increase in parenteral nutrition usage duration and a 4-fold greater prevalence of NEC was seen in the early empiric antibiotic-exposed neonates, when compared with control infants ( P < 0.01). Early empiric antibiotic exposure appears to negatively influence preterm infant feeding tolerance and possibly contributes to NEC.